Water Quality Investigation of the Old Repas DAM in Bentong Pahang - Noa, Gaga Naeqe (2017)
The land development and agricultural activities within the catchment of the Old Repas Dam in Bentong, Pahang is expected to cause deterioration in water quality due to contaminants getting into the water bodies from various non-point sources (NPS) which were picked up by surface run-offs occurring due to precipitation. Traces of heavy metals common to tin mining areas should also be a problem as tin mining was a common activity within the watershed. Furthermore, water discolouration is common on the downstream of the dam which may signify water contamination. To fully understand the effect of the water discoloration at the downstream of the dam, a total of 8 water samples were collected from 4 selected critical sampling points. The sample were then tested on 11 parameters including 5 heavy metals common to areas popular with tin mining and the remaining 6 parameters are those required for calculation of the water quality index (WQI). The five selected heavy metals are Arsenic (As), Copper (Cu), Lead (Pb), Tin (Sn) and Zinc (Zn). The remaining six parameters required for WQI calculations are Dissolved Oxygen(DO), BOD5, COD, Suspended Solids (SS), pH and Ammoniacal Nitrogen (AN). The water was first analysed using each parameter separately before combining them to determine the WQI. The two samples taken for each sampling points represents the water quality on two different weather condition one being dry and the other after heavy rainfall. The water quality was generally lower after the rainfall on most of the parameters except DO. The selected heavy metals were all found to be within the natural levels (or absent) on both sampling days except at one of the sampling point having a very high Tin concentration resulting from the wet weather. By taking the average of the WQI value, the water at each of the four sampling points were classified into their respective classes and a short statement was given to describe the samples. Two Sampling points are classified Class II and is considered clean while the other two were classified as Class III and are slightly polluted. Recommendations were given on how the two slightly polluted sampling points can be improved.